Ecophysiological Responses of Five Mangrove Species (Bruguiera gymnorrhiza, Rhizophora stylosa, Aegiceras corniculatum, Avicennia marina, and Kandelia obovata) to Chilling Stress - Wang, Shu-Min; Wang, You-Shao; Su, Bo-Yu; Zhou, Yue-Yue; Chang, Li-Fang; Ma, Xiao-Yu; Li, Xiao-Mei (Frontiers in Marine Science, 2022)
Although low temperature is a critical growth constraint on plants, the physiological mechanism remains unclear especially in mangrove plants. Hence, the morphological characteristics of five mangrove plants (B.gymnorrhiza, R.stylosa, A.corniculatum, A.marina and K.obovata) were compared under chilling stress. The contents of hydrogen peroxide (H2O2), malondialdehyde (MDA) and proline were tested. Activities of ROS-scavenging enzyme (SOD, POD and CAT) were also measured after chilling stress. It was concluded that K.obovata can well tolerate to chilling stress and B. gymnorrhiza suffered the most severe chilling damage. Leaf-morphology observation exhibited the K.obovata and A.corniculatum can sustain chilling stress when the B.gymnorrhiza wilted and A.marina turning brown. The content of H2O2 exhibited increased at first and subsequently decreased trend in all plants. MDA instantaneously increased in B. gymnorrhiza and R.stylosa but changed slowly in K.obovata and A.corniculatum. High content of proline accumulated in B.gymnorrhiza and K.obovata. The activities of the superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) increased at first and then decreased in all mangrove species. The antioxidants maintained high-activity in K.obovata while decreased earliest in A.marina exposed to long-term chilling stress. Principal component analysis (PCA) indicated that high antioxidant enzyme activities play key roles in chilling tolerance for mangrove plants. The longer-term chilling tolerance of K.obovata may be related to the high antioxidant enzyme activities and proline accumulation. Lower H2O2 and MDA content strengthen the anti-chilling ability of A.corniculatum. Further investigation on the molecular will facilitate the understanding of the anti-chilling mechanism of mangrove plants.